Factors affecting the professional skepticism of independent auditors in Viet Nam - Thu Trang Ta; Thanh Nga Doan; Duc Cuong Pham; Hoai Nam Tran (Cogent Business & Management, 2022)
The study investigates the key factors affecting the professional skepticism of independent auditors in Vietnam. The factors that are studied in this research include knowledge and experience, workload, time pressure, and incentives that affect professional skepticism of independent auditors. The authors have utilized quantitative and qualitative analyses in combination with a logistic regression model and other available analytical tools for conducting the research in SPSS software. All the statistics processed in the paper were based on 90 independent Vietnamese auditors in 2021. The results reveal that factors including knowledge, experience, and incentives positively affect professional skepticism, while workload and time pressure negatively impact professional skepticism. The findings suggest Vietnamese lawmakers and auditing firms should regulate annual training courses for auditors to enhance their professional ability and reasonably encourage the auditor’s motivation, while it is necessary to minimize workload and time pressure for auditors in order to maintain and improve the audit quality. This implication could be applied for Vietnamese auditing firms and international auditing firms.